Synthesis, Characterization and Biocidal Evaluation of Azole-Based Ligandsmetal Complexes - Olagboye, S. A.; Hassan, G. F. (International Journal of Applied Sciences and Biotechnology, 2013)
Different metal complexes of the azole-based ligands have been synthesized and characterized based on the solubility, percentage yield, melting points and conductivity a well as the antimicrobial evaluations on the selected fungi species of plant pathogens. The studies revealed that solid metal complexes were soluble in 80% water and 20% (DMSO) dimethylsulphuroxide and the percentage yields were of appreciable high while the conductivity results showed that metal complexes were non-electrolytes. The solid complexes were also screened against the fungi species: Rhizoctonia solani,Pythium aphaindermatum,Rhizoctonia cerealis,Sclerotium rofisil ,Phyphotoria palmivora (causative agent of black pod diseases) and Benlate a commercial anti fungi agent (as control).The results of the present studies confirmed that metal complexes had good inhibitory actions on the growth of the fungi species and metal complexes appeared to be more proactive on the tested organisms than the free ligands. DOI: http://dx.doi.org/10.3126/ijasbt.v1i4.9176 Int J Appl Sci Biotechnol, Vol. 1(4): 258-265